The effect of unsupported arm elevations on regional chest wall volumes and thoracoabdominal asynchrony in patients with chronic obstructive pulmonary disease. (2nd November 2022) - Kruapanich, Chathipat; Tantisuwat, Anong; Thaveeratitham, Premtip; Lertmaharit, Somrat; Ubolnuar, Nutsupa; Chimpalee, Jaturong; Mathiyakom, Witaya
ABSTRACT: Objective: To compare the effect of unsupported arm elevation (UAE) in different planes on chest wall volumes, thoracoabdominal asynchrony (TAA), ventilatory demands, dyspnea, and arm fatigue in patients with chronic obstructive pulmonary disease (COPD) and healthy subjects. Methods: Twenty-one patients with COPD and healthy-matched subjects performed UAE in shoulder flexion, scaption, abduction, and resting. Pulmonary total and regional chest wall volumes ( V RCp ), abdominal rib cage volume, abdominal volume, TAA, and ventilatory demands during arm positions were measured using optoelectronic plethysmography. Results: In both groups, V RCp and TAA were significantly affected during UAEs compared with the resting position. The healthy subjects had significantly decreased V RCp (L) ( p < 0.05) during scaption (0.14 ± 0.07) and abduction (0.15 ± 0.06) than during flexion (0.18 ± 0.07) and no significantly different TAA between UAEs. The COPD group had no significantly different V RCp between UAEs, had significantly increased TAA ( p < 0.05) during scaption (31.1°±9.5°) and abduction (32.3°±9.9°) than during flexion (29.7°±9.1°); and had significantly worse V RCp ( p = 0.007), TAA ( p = 0.0001), ventilatory demands ( p < 0.05), dyspnea (( p = 0.03), and arm fatigue ( p = 0.002). Conclusions: In patients with COPD, UAE in different planes similarly restricted the upper chest wall volume. Shoulder scaption and abduction significantly impaired TAA, ventilation, dyspnea, and arm fatigue compared with flexion. These results may help to select the appropriate UAE during physical activities.